Growth and quality enhancement of young Labisia pumila benth. and hook. f. varieties under organic and inorganic fertilisation - Rosni, Nurrul Akmar (2019)
The application of organic and inorganic fertiliser to the plant is considered as a good agricultural practice because it improves the plant growth and its quality. A study was conducted with the objectives: (i) to determine growth and quality of different varieties of Labisia pumila with different sources of fertilisers at 90 kg N/ha; (ii) to determine the best rate of organic and inorganic fertiliser in enhancing growth and secondary metabolites production of L. pumila and (iii) to determine and characterize phytochemical quality of L. pumila leaves extract as the result of fertilizer application. There were two experiments conducted to fulfil the objectives. The treatments were designed in a randomized complete block design (RCBD). In the first experiment, two varieties of L. pumila (alata and pumila) and four different sources of fertiliser at 90 kg N/ha (chicken manure, Gobi, NPK green and control) were used to determine the optimum growth and quality of L. pumila. There were higher interactions among all factors recorded on total biomass and photosynthesis activity on organic fertilisers (p≤0.05). Chicken manure and Gobi were statistically different on leaf gas exchange (p≤0.01) and secondary metabolites (p≤0.05) of L. pumila. The experimental results of this study have shown that the Gobi and chicken manure produced a higher effect leaf gas exchange and secondary metabolites of on L. pumila varieties compared to NPK green. High amount of secondary metabolites (total phenolic and flavonoid) and leaf gas exchange recorded give preference to the use of organic than inorganic fertiliser. In the last experiment, four N rates (0, 30, 60 and 90 kg N/ha) and two types of fertiliser (Gobi and NPK green) were used to determine growth and quality of L. pumila var alata at different harvesting stages. The effect of the main interaction among all factors was particularly on nutrient content (p≤0.01) and secondary metabolites (p≤0.01). The NPK green at 90 kg N/ha at 15 WAT had higher N content (1.24%) and at 60 kg N/ha at 10 WAT recorded higher nitrate content (3.715 mg/l). Gobi at 90 kg N/ha showed the higher secondary metabolites at 10 WAT. Thus, the phytochemical content of Gobi from the above treatment was determined quantitatively using TLC analysis with quercetin (88532 a.u), kaempferol (61226 a.u), gallic acid (84559.5 a.u), cinnamic acid (43828.5 a.u) and ferulic acid (63336 a.u) found abundant in plant extracts by using qTLC appweb. Gobi at 90 kg N/ha is a good resource on leaf gas exchange, secondary metabolites and the compositions in TLC analysis of L. pumila as compared to NPK green. Harvesting L. pumila at age from 26 to 31 weeks showed significant production of secondary metabolites probably due to plants were saturated with nitrogen. Both experiments have proven that organic fertilisers can produce higher quality of L. pumila compared to NPK green when harvested at 15 weeks after transplanting. The availability of N due to the slower release of N from organic fertiliser during the growing season and through additional soil N availability may affect the photosynthesis of plant by altering the synthesis of secondary compounds by applying suitable complete fertiliser sources. The carbon surplus, which was not utilized for growth due to the slow release of nutrients from the organic fertiliser, was allocated to the production of secondary metabolites, in particular phenolics. This followed the principle of growth-differentiation balance (GDB) hypothesis that states an imbalance in carbon and nutrient will allow plant to excess resource for secondary metabolites production.